If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1Y = -20 Solving 4 + -1Y = -20 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1Y = -20 + -4 Combine like terms: 4 + -4 = 0 0 + -1Y = -20 + -4 -1Y = -20 + -4 Combine like terms: -20 + -4 = -24 -1Y = -24 Divide each side by '-1'. Y = 24 Simplifying Y = 24
| 8(r+4)=-7(-5-r) | | 12n+3=13n-6 | | 14-6.2x(-3+-7)= | | -4x-8(4)=24 | | 4(c+0)=2x+6 | | 148=-8(-6+2x)-4x | | 3x(-8)-2x(-5)= | | px-t=k | | 6.8=15.8+3b | | 3g+5=7b+4 | | 8j-14=-22 | | 8(2x+3)=7(4x-2) | | 3x+10=-1 | | 180-104= | | (X+1)2=y | | 3(2x+-4)=9-3(x+1) | | 6(3-x)=8x-10 | | y=2*-1+4 | | -9=3 | | 148=-8(-6-4x)-4x | | 3p+7=9+2p | | 10h+12=8h+5 | | 54-2x=3x-1 | | -3b^2-11b=-15 | | 1.5x=6.25+1.25x | | 1.5x=6.25+1.25x | | 10-(5x-36)=-(50+7x) | | -11=-2+4 | | -h+7=-14 | | -h+7=-14 | | -h+7=-14 | | -h+7=-14 |